Medicine in Ancient Assur : A Microhistorical Study of the Neo-Assyrian Healer Kiṣir-Aššur - Arbøll, Troels Pank (Ancient Magic and Divination, 2020)
In Medicine in Ancient Assur Troels Pank Arbøll offers a microhistorical study of a single exorcist named Kiṣir-Aššur who practiced medical and magical healing in the ancient city of Assur (modern northern Iraq) in the 7th century BCE. The book provides the first detailed analysis of a healer's education and practice in ancient Mesopotamia based on at least 73 texts assigned to specific stages of his career. By drawing on a microhistorical framework, the study aims at significantly improving our understanding of the functional aspects of texts in their specialist environment. Furthermore, the work situates Kiṣir-Aššur as one of the earliest healers in world history for whom we have such details pertaining to his career originating from his own time.